Solitary confinement : effects, practices, and pathways toward reform - Lobel, Jules; Smith, Peter Scharff, 1971- (New York, NY : Oxford University Press, 2019)
Solitary confinement is used for a variety of different reasons in many prison systems all over the world, despite the fact that research shows that these practices have widespread and pronounced negative health effects. Besides the death penalty, solitary confinement is arguably the most punitive and dangerous intervention available to state authorities in democratic nations. This broad and interdisciplinary text draws together research and personal experience from neuroscientists, high level prison officials, social and political scientists, medical doctors, lawyers, and former prisoners and their families from different countries in order to address the effects and practices of prolonged solitary confinement and to strengthen the movement for its reform and eventual abolition.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 15, 2019).
Keywords: Solitary confinement; Prisons